The contextual integrity of the closet: Privacy, data mining and outing Facebook's algorithmic logics. (1st March 2017) - Werbin, Kenneth C.; Lipton, Mark; Bowman, Matthew J.
In the 2010 book The Facebook Effect by David Kirkpatrick, Facebook founder Mark Zuckerberg made the claim that 'users have one identity'. Through a critical theoretical analysis of a series of case studies of people being outed by Facebook, this article argues that 'one identity' and Facebook's use of algorithms to drive profits are fundamentally incongruous with prevailing intersectional scholarship. The case studies articulate a theoretical framework that ties intersectional conceptions of gender and sexuality to social media and privacy. By aligning intersectional and privacy theories, the article argues that 'one identity' constitutes a violation of privacy norms as conceptualized by Helen Nissenbaum's framework of contextual integrity. The article concludes that Facebook is anathema to the privacy and real life experiences of its users, which cannot fit into static categories and which change over time, mitigating the potential for the performance of fluid and intersectional identities.